2016
DOI: 10.1016/j.jvb.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitive predictors of academic persistence and performance in engineering: Applicability across gender and race/ethnicity

Abstract: We examined the utility of social cognitive variables in the longitudinal prediction of academic persistence and success of engineering students. The participants, 908 students enrolled in engineering majors at two state universities, completed measures of academic support, self-efficacy, outcome expectations, interests, satisfaction, positive affect, and intended persistence at the end of each of their first four semesters. In the current study, students' first and second semester responses were used to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
5
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 26 publications
9
82
5
5
Order By: Relevance
“…Our findings are thus an expansion of the very scarce research on pre-higher education self-efficacy, and the even scarcer research on its association with attrition, as it represents the first multi degree program study on this relationship. Furthermore, our findings are in line with the research where self-efficacy is measured during degree programs, typically during the first semester, as they find that low self-efficacy is associated with increased attrition, increased risk of withdrawal, decreased intention to persist, and decreased intention to complete (De Clercq, Galand & Frenay, 2017;Elliot, 2016;Lent et al, 2016;Thomas, 2014;Vuong, Brown-Welty & Tracz, 2010;You, 2018).…”
Section: Discussion and Future Directionssupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are thus an expansion of the very scarce research on pre-higher education self-efficacy, and the even scarcer research on its association with attrition, as it represents the first multi degree program study on this relationship. Furthermore, our findings are in line with the research where self-efficacy is measured during degree programs, typically during the first semester, as they find that low self-efficacy is associated with increased attrition, increased risk of withdrawal, decreased intention to persist, and decreased intention to complete (De Clercq, Galand & Frenay, 2017;Elliot, 2016;Lent et al, 2016;Thomas, 2014;Vuong, Brown-Welty & Tracz, 2010;You, 2018).…”
Section: Discussion and Future Directionssupporting
confidence: 90%
“…Devonport and Lane (2006) also found an association between low levels of self-efficacy (on a self-developed academically related instrument) in first year university students, and an increased risk of withdrawal. The relationship between academic self-efficacy and student attrition has also been studied through students' self-perceived intention to persist in HE and several studies have found a positive association between high levels of academic self-efficacy and an increased completion intention (Elliot, 2016;Lent et al, 2016;Thomas, 2014;Vuong, Brown-Welty & Tracz, 2010;You, 2018). However, none of the studies investigating self-efficacy either pre-HE or after commencement to HE looked into the issue of measurement invariance across subgroups such as academic discipline, degree program or institution.…”
Section: Introductionmentioning
confidence: 99%
“…This funding has allowed researchers to do large-scale theory-based systematic research, including longitudinal research, across genders and racial/ethnic minority populations. Lent and his colleagues (e.g., Lent et al, 2015;Lent et al, 2016;Lent et al, 2013, Lent, Sheu, Gloster, & Wilkins, 2010 have studied engineering students at predominantly White institutions and historically Black universities across several years, finding support for the SCCT. Flores and Navarro and their colleagues (e.g., H. Lee, Flores, Navarro, & Kanagui-Munoz, 2015;Navarro, Flores, Lee, & Gonzalez, 2014;Navarro et al, 2019) used the same theoretical model to study Hispanics and Whites in predominantly White institutions and Latinx serving institutions, also finding support for the model.…”
Section: Weaknesses and Threats In 2019mentioning
confidence: 99%
“…In particular, it is unclear whether early indicators of prior performance like the SAT drive both attitudes about science, subsequent course performance and persistence, or whether course performance alone drives persistence. Longitudinal analyses testing this mechanism in engineering used a cumulative measure of college grade point average (GPA) to show that a more proximal indicator of performance is a stronger predictor of persistence than relatively distal standardized application test scores for both men and women (Lent et al, ). Few studies have examined how relative performance in specific disciplines may provide differential feedback to influence gendered persistence in science and health‐related fields.…”
Section: Theoretical Frameworkmentioning
confidence: 99%